Peculiarities of legal regulation of activities of the National Police of Ukraine in the field of ensuring information security in Ukraine - I. D. Kazanchuk; V. P. Yatsenko (Law and Safety)
Based on the analysis of scientific concepts and legal principles the author has provided the definition of information security, provision of information security in Ukraine and has characterized its components. The current state of legal regulation of the organization and activity of cyberpolice units of the National Police of Ukraine has been analyzed. Particular attention has been paid to the legal analysis of the tasks, functions and structure of the Cyberpolice Department of the National Police of Ukraine. Special attention has been drawn to certain shortcomings of Ukrainian legislation in the field of ensuring information security by the police, its compliance with the norms and standards of international law. Taking into account the specifics of the tasks, the author has provided characteristics of the functions of cyberpolice units in the information sphere, which should be divided according to the purpose into: 1) basic (external), which are focused on law enforcement and preventive aspects; 2) auxiliary (intrasystem), which are focused on promoting the implementation of basic functions, the introduction of appropriate management mechanisms within the system.